Resposta :
Conta armada:
[tex]x = ( - 2)^{ - 3} - 3^{2} +[( - \frac{1}{2} )^{ - 3} \times {2}^{ - 1} ] \div ( \frac{1}{4})^{ - 1} \: \\ [/tex]
Agora, o cálculo:
[tex]x = - 8 - {3 }^{2} + [( - \frac{1}{2} ) ^{ - 3} \times {2}^{ - 1} ] \div ( \frac{1}{4})^{ - 1} \\ \\ x = - 8 - 9 + ( - 2 ^{ 3} \times {2}^{ - 1} ) \div ( \frac{1}{4})^{ - 1} \: \\ \\ x = - 8 - 9 + ( - 2 ^{ 2} ) \div ( \frac{1}{4})^{ - 1} \\ \\ x = - 8 - 9 + ( - 4 ) \div ( \frac{1}{4})^{ - 1} \\ \\ x = - 8 - 9 - 4 \div ( \frac{1}{4})^{ - 1} \\ \\ x = - 8 - 9 - 4 \div 4 \\ \\ x = - 8 - 9 - 1 \\ \\ x = - 18[/tex]
O resultado é x = -18
→ Aprenda sobre potenciação em:
https://brainly.com.br/tarefa/5146130
https://brainly.com.br/tarefa/12841416
→ Aprenda a calcular contas com frações em:
https://brainly.com.br/tarefa/22325832
https://brainly.com.br/tarefa/31694851
Bons estudos!